Pengujian Emisi Gas Buang Sepeda Motor Dengan Bahan Bakar Premium - Lelawati Lelawati (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2019)
Exhaust emissions are waste products of fuel combustion from inside the machine issued through the exhaust system. Premium fuel is a fuel consisting of a mixture of hydrocarbon liquid are very volatile which has an octane rating of 88 ron. Premium is the product Pertamina which contains C2H6- C6H14 with a minimum content of sulfur (S) 0.05%, Lead (Pb) 0.0013%, and oxygen (O) of 2.7%. Motor fuel is such a machine types of calories that converts chemical energy of fuel into mechanical energy